Salidroside attenuates neuronal ferroptosis by activating the Nrf2/HO1 signaling pathway in Aβ1-42-induced Alzheimer's disease mice and glutamate-injured HT22 cells - Sixia Yang; Zeping xie; Tingting Pei; Yi zeng; Qiaowu Xiong; Hui Wei; Yong Wang; Weidong Cheng (BMC, 2022)
Abstract Background Alzheimer's disease (AD) is a neurodegenerative disease. Ferroptosis plays a critical role in neurodegenerative diseases. Nuclear factor E2-related factor 2 (Nrf2) is considered an important factor in ferroptosis. Studies have demonstrated that salidroside has a potential therapeutic effect on AD. The intrinsic effect of salidroside on ferroptosis is unclear. The purpose of this study was to investigate the protective effects and pharmacological mechanisms of salidroside on alleviating neuronal ferroptosis in Aβ1−42-induced AD mice and glutamate-injured HT22 cells. Methods HT22 cells were injured by glutamate (Glu), HT22 cells transfected with siRNA Nrf2, and Aβ1−42-induced WT and Nrf2−/−AD mice were treated with salidroside. The mitochondria ultrastructure, intracellular Fe2+, reactive oxygen species, mitochondrial membrane potential, and lipid peroxidation of HT22 cells were detected. Malondialdehyde, reduced glutathione, oxidized glutathione disulfide, and superoxide dismutase were measured. The novel object recognition test, Y-maze, and open field test were used to investigate the protective effects of salidroside on Aβ1−42-induced WT and Nrf2−/−AD mice. The protein expressions of PTGS2, GPX4, Nrf2, and HO1 in the hippocampus were investigated by Western blot. Results Salidroside increased the cell viability and the level of MMP of Glu-injured HT22 cells, reduced the level of lipid peroxidation and ROS, and increased GPX4 and SLC7A11 protein expressions. These changes were not observed in siRNA Nrf2 transfected HT22 cells. Salidroside improved the ultrastructural changes in mitochondria of HT22 cells and Aβ1−42-induced AD mice, but not in Aβ1−42-induced Nrf2−/−AD mice. Salidroside increased protein expression levels of GPX4, HO1, and NQO1 and decreased protein expression of PTGS2 in Aβ1−42-induced AD mice but not in Aβ1−42-induced Nrf2−/−AD mice. Conclusions Salidroside plays a neuroprotective role by inhibiting neuronal ferroptosis in Aβ1−42-induced AD mice and Glu-injured HT22 cells, and its mechanism is related to activation of the Nrf2/HO1 signaling pathway. Graphical Abstract